Is culture the key? Emotional intelligence, autonomous motivation and physical activity of student-athletes from China and Russia - Rogaleva, Liudmila Nikolaevna; Zhong, Tao; Garcia-Mas, Alexandre (Frontiers in Psychology, 2024)
Emotional intelligence is considered as an important factor impacting on sports motivation of students-athletes. Meanwhile the role of culture in the development of emotional intelligence is still insufficiently studied in sports psychology. The purpose of the study included comparing the indicators of emotional intelligence of student-athletes in China and Russia, identifying the relationship between emotional intelligence, sports motivation and physical activity, as well as studying the prognostic effect of emotional intelligence on autonomous motivation. The research was done among 474 student- athletes. In Chinese students sample (N = 281), the 163 men and 118 women. In the Russian student sample (N = 193), there were 64 men and 129 women. The following research methods were used: emotional intelligence scale, the sport motivation scale-6, the international physical activity questionnaire. The results of the study have showed that the level of emotional intelligence of Chinese student-athletes is higher than that of Russian students-athletes. Positive correlations between emotional intelligence, autonomous motivation and physical activity were found in both samples. At the same time, the correlation coefficient in the Russian sample was lower. A predictive relationship between emotional intelligence and autonomous motivation has been established; meanwhile the self-assessment of emotions and emotion regulation make the greatest contribution to autonomous motivation in the Chinese sample, while in the Russian sample there is only the use of emotions. Considering the cultural context can contribute to the preparation effective programs for the development of emotional intelligence and autonomous motivation for physical activity.